Kafalah dalam Perspektif Islam: Kajian Komprehensif dari Al-Qur'an, Hadis, dan Ulama Serta Implementasinya dalam Lembaga Keuangan - Afia Apriyanti; Wahyu Bahrul Alam; Alvian Syachrul Nasruloh (STAI Nurul Qadim, 2024)
Islam regulates social interaction in the Quran and Hadith. One type of muamalah in Islam is kafalah, which is a guarantee or responsibility. This study aims to understand kafalah from the perspective of the Quran, hadith, positive law, and its application in daily life. The method in this study uses library research and qualitative methodology, which proved effective in exploring and describing the phenomenon under study in detail. The results of the study. First, Kafilah is an insurer's promise to a third party that the second party or the insured can fulfill his obligations. Second, kafil is one of the pillars and conditions of kafalah: makful anhu, makhful bih, and shighat. Third, one of the types of kafalah includes kafalah bin al-nafs, kafalah bial-mal, kafalah in the form of objects, and kafalah related to disgrace. Fourth, legal regulations from the Qur'an and hadith. Surah Yusuf verses 72, 66, and 78, Bukhari No. 2131, An-Nasa'i No. 4613, and Ibn Majah 2398. DSN Fatwa regarding kafala No. IX: 11/DSN-MUI/IV/2000, which is regulated in article 20, paragraph 12 of KHES. Fifth, hadith and fiqh experts argue that kafalah is not just a contract but also an implementation of Islamic values such as helping and justice. Sixth, the application of kafalah in everyday life: Bank guarantees, kafalah contracts in the banking sector, kafalah in the Healthy Indonesia Card program, kafalah in Sharia Letters of Credit, and Islamic banking insurance